A Case Study of the Audiovisual Translation of Wordplay: A Touch of Cloth - Camilli, Lana Pierrina (Journal of Audiovisual Translation, 2019)
This paper examines the dubbing of the British comedy series A Touch of Cloth into French. Building on existing descriptive theory regarding wordplay translation – particularly the model of translation techniques laid out by Delabastita (1993) – translation patterns are identified. A corpus of instances of wordplay is established, correlations are identified between particular types of wordplay and particular translation results, and a case-by-case examination is undertaken to determine how different factors impacted these results. A wide range of factors are found to contribute to the way wordplay is translated, notably: the languages at hand, the nature of the joke, and the audiovisual features the joke brings into play. Conclusions are then drawn regarding the technique likely to be employed on a given occasion and why, as well as how closely the translation can be expected to reflect the original segment.